K teorii mezijazykové interference v lexikálním plánu češtiny a polštiny - Muryc, Jiří (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2015)
The article deals with the theory of language interference in the lexis of Czech and Polish languages. The author defines the term, specifies several types of interference, and describes some aspects of Czech and Polish lexical typology. Based on particular occurrences the author offers classification into three basic types of lexical interference, so called lexical transfers.
Keywords: interference; lexis; Czech language; Polish language; translation